Kecakapan Literasi Digital Para Penyintas Online Gender-Based Violence - Andiyansari, Popi; Juwono, Andri Prasetyo (Program Studi Ilmu Komunikasi, 2024)
The digital literacy index in Indonesia continues to increase. However, apart from increasing the literacy index, the number of online gender-based violence (online GBV) is in the high category. This research aims to determine the level of digital literacy skills of survivors of online gender-based violence in the Special Region of Yogyakarta. This research aims to understand the digital literacy skills of online GBV completers so that it becomes a consideration for related parties in efforts to improve digital literacy skills. This research was studied using 10 digital literacy competencies by Japelidi. This research uses a qualitative descriptive method with the research object being eight online GBV editors in the DIY area. The results of this research indicate that participants have not fulfilled the evaluation and collaboration competencies on digital platforms. Participants have not been able to choose the correct content and only follow the opinions of other people (netizens). Participants also have not been able to use their critical powers to initiate communities on online platforms to resolve online GBV problems.